The influence of government incentives on electric vehicle adoption: Cross-national comparison - Sarah Fluchs; Garnet Kasperk (Philipps-University Marburg, School of Business and Economics, 2017)
This paper examines the influence of political incentives which are set by the government and aim at promoting the adoption of electric vehicles (EVs). More specifically, battery electric vehicles (BEVs) and plug-in hybrid elec- tric vehicles (PHEVs) are considered. A classification and categorization of different incentives is provided and specified for five countries, namely Norway, Netherlands, Germany, United States and China. Additionally, an empirical study was performed for China and the Netherlands employing the method of time series (TS) analysis. Results reveal that government incentives affect EV market penetration but exact effects differ for both country and type of EV. In China, especially direct rebates increase EV adoption under certain circumstances. In the Netherlands, PHEVs' market share increases more compared to BEVs' market share if both vehicle types receive the comparable incentives.
Keywords: 330; public policy; electric vehicles; political incentives; technology diffusion